Calvarial graft resorption index in the reconstruction of the maxillary sinus in patients with atrophic maxillas: a prospective clinical study - Macedo, R. L.L.; Ponzoni, D. [UNESP]; Vedovatto, E.; de Carvalho, F. A.; de Carvalho, P. S.P. (Elsevier, 2021)
The objective of this study was to assess the resorption index of particulate calvarial grafts in maxillary sinuses of patients undergoing total reconstruction of an atrophic maxilla with residual alveolar bone that was less than, or equal to, 3 mm thick. Twenty-one maxillary sinus floor elevations were carried out using particulate calvarial grafts in 11 individuals with totally edentulous maxillas. All patients had computed tomography (CT) before (T0), and 48 hours (T1) and six months after surgery (T2). For each CT scan, linear measurements were taken of sections of the anterior, medial, and posterior regions of the maxillary sinus. There was a significant increase in the height of the maxillary sinus floor when T0 was compared with T1 (p = 0.001). There was a statistically significant reduction in all maxillary sinus measurements when T1 was compared with T2; the mean height reduction being 2.36 mm (16.87%) in the anterior region, 3.53 mm (22.47%) in the medial region, and 2.21 mm (22.78%) in the posterior region (p = 0.001). Mean resorption was 20.7%. Autogenous calvarial bone used alone is an option for graft material in pneumatised maxillary sinuses and in cases where there is limited alveolar bone.
Keywords: autogenous bone graft; calvaria; elevation of maxillary sinus floor